2019
DOI: 10.1080/16184742.2019.1631365
|View full text |Cite
|
Sign up to set email alerts
|

Sponsees matter! How collective responsibility judgments of sport sponsors affect sponsee equity

Abstract: Research question: Previous research has focused on sport sponsors, with little known on how sponsorship affects sponsee equity (e.g. audiences' behaviors towards sponsees). Further, sponsorship research typically ignores concurrent sponsors, which are naturally perceived in terms of perceived 'groupness' (entitativity). In turn, entitativity will affect people's judgments of the collective responsibility (CR) sponsors have towards the properties they are associated with. To compound the issue, sponsees' depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Moreover, most research focuses on the effects that sponsorship generates for sponsor, neglecting the sponsee's point of view [37]. Among the exceptions, we highlight the study by Dickenson and Souchon (2019), in which the relationships linking multiple sponsors to a single sponsee are analyzed [38]. In this specific case, multiple sponsors represent an aggregate of social entities perceived as a single whole [39], which, according to social psychology, can be expressed in terms of entitativity [40,41].…”
Section: Literature Analysis On the Sponsor-sponsee Relationshipmentioning
confidence: 99%
“…Moreover, most research focuses on the effects that sponsorship generates for sponsor, neglecting the sponsee's point of view [37]. Among the exceptions, we highlight the study by Dickenson and Souchon (2019), in which the relationships linking multiple sponsors to a single sponsee are analyzed [38]. In this specific case, multiple sponsors represent an aggregate of social entities perceived as a single whole [39], which, according to social psychology, can be expressed in terms of entitativity [40,41].…”
Section: Literature Analysis On the Sponsor-sponsee Relationshipmentioning
confidence: 99%
“…Finally, future research may consider a more precise segmentation of post-related contents. For instance, Dickenson and Souchon (2019) have recently found that collective responsibility of sponsors can lead to a positive perception of both sponsors and sponsees. Further research could develop field experiments to investigate reactions to controlled content in order to derive more robust and causal interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that when it comes to sponsorship, marketing managers still depend on their instinct rather than market research (Woisetschläger et al, 2017), and the influence of sponsors on sponsored properties is both largely overlooked and important in practise (Dickenson & Souchon, 2020). As a result, our study intends to understand the role of media in sponsorship from a B2B perspective (i.e.…”
Section: Business-to-business Relationship In Sponsorshipmentioning
confidence: 99%
“…There have been progressively rapid improvements in the field of sponsorship in the last 30 years and is one of the fastest growing areas of marketing (Mazodier, Henderson, & Beck, 2018;Woisetschläger, Backhaus, & Cornwell, 2017), whilst rapidly becoming a popular form of marketing communication (Dens, De Pelsmacker, & Verhellen, 2018;Dickenson & Souchon, 2020;Mazodier & Rezaee, 2013). Sponsorship growth is at a rate of 4.9 percent globally -higher than the other marketing communication tools such as advertising and promotion (International Event Group, 2018), and projected to reach USD89.6 billion in 2027 (Statista, 2021).…”
Section: Introductionmentioning
confidence: 99%